Notes on two species of Calostoma (Calostomataceae, Boletales) from the south of China - Xu, Chang; Liang, Zhi-Qun; Jiang, Shuai; Zhang, Ping; Huang, Sheng-Zhuo; Zeng, Nian-Kai (Phytotaxa, 2022)
Several collections of Calostoma (Calostomataceae, Boletales) from the south of China were investigated using morphology, and molecular phylogenetic analyses of DNA sequences from the nuc 28S rDNA D1-D2 domains (28S), and the nuc rDNA internal transcribed spacer (ITS). Two species of the genus are recognized, one is the previously described taxon, C. areolatum, the other, C. sinocinnabarinum, is described as new: Detailed descriptions, color photos of fresh basidiomata and line-drawings of microstructures of the two taxa are presented.